ANALYSIS OF POWER OF ATTORNEY TO SELL AS A REQUIREMENT FOR MURABAHAH BIL WAKALAH FINANCING AT BANK SYARIAH INDONESIA - Delia Sariyulis; Muhammad Iqbal (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2025)
This article analyzes the power of attorney to sell as a condition for murabahah bil wakalah financing at Bank Syariah Indonesia. A power of attorney to sell is a legal document that authorizes a particular party to sell assets or goods on behalf of another party. This power of attorney is regulated in Article 1792 of the Civil Code. In this financing, the intended party is a Sharia Financial Institution. In murabahah bil wakalah financing, a power of attorney to sell is crucial because it guarantees the Sharia financial institution in the transaction process. With this power of attorney, financial institutions can ensure they have the right to sell the financed goods if the customer fails to fulfill their obligations. The use of this SKM raises several problems in Islamic jurisprudence, because it concerns the status of ownership of goods, the principle of justice, and the validity of the transfer of rights through a power of attorney in the context of a Sharia sale and purchase agreement, as this SKM is irrevocable or cannot be revoked. The type of legal research used is an empirical juridical approach. Legal materials were collected through literature studies, document studies, and through interviews and observations. The research concludes that the use of a power of attorney for murabahah bil wakalah financing at Bank Syariah Indonesia is valid because the SKM does not conflict with sharia principles, especially in the wakalah contract, as long as the granting of power of attorney is carried out voluntarily by the customer, with a complete understanding of its contents and consequences. This is expected to provide recommendations for financial institutions and customers in understanding and good practices related to using a power of attorney for selling.